2005
DOI: 10.1186/1472-6947-5-16
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based patient choice: a prostate cancer decision aid in plain language

Abstract: BackgroundDecision aids (DA) to assist patients in evaluating treatment options and sharing in decision making have proliferated in recent years. Most require high literacy and do not use plain language principles. We describe one of the first attempts to design a decision aid using principles from reading research and document design. The plain language DA prototype addressed treatment decisions for localized prostate cancer. Evaluation assessed impact on knowledge, decisions, and discussions with doctors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 27 publications
2
93
0
2
Order By: Relevance
“…[30][31][32][33][34] Only 1 study reported data concerning the length of 38 In general, participants found DAs to be helpful and were satisfied with the content. Brink et al 41 and Holmes-Rovner et al 36 reported data concerning the clarity and usefulness of the DAs themselves. In the study by Brink et al, 79% of participants thought the amount of information presented was appropriate and 91% were satisfied with the presentation and narration 41 ; in the study by Holmes-Rovner et al, greater than 75% of the participants thought the length of the presentation and the amount of information presented were "about right," and the treatment descriptions were balanced.…”
Section: How Acceptable and Feasible Is The Use Of Das In Practice?mentioning
confidence: 99%
See 4 more Smart Citations
“…[30][31][32][33][34] Only 1 study reported data concerning the length of 38 In general, participants found DAs to be helpful and were satisfied with the content. Brink et al 41 and Holmes-Rovner et al 36 reported data concerning the clarity and usefulness of the DAs themselves. In the study by Brink et al, 79% of participants thought the amount of information presented was appropriate and 91% were satisfied with the presentation and narration 41 ; in the study by Holmes-Rovner et al, greater than 75% of the participants thought the length of the presentation and the amount of information presented were "about right," and the treatment descriptions were balanced.…”
Section: How Acceptable and Feasible Is The Use Of Das In Practice?mentioning
confidence: 99%
“…Six DAs discussed "watchful waiting," surgical options, and radiation therapy (external beam radiation or brachytherapy). 33,[35][36][37]40,42 Four DAs also discussed hormonal or combination therapy. 33,37,42,43 One trial discussed surgery and radiation therapy only, 32 and 3 DAs described radiation therapy only.…”
Section: Types Of Das and Control Interventionsmentioning
confidence: 99%
See 3 more Smart Citations